Gaya Hidup Penderita Diabetes Melitus di Puskesmas Payung Sekaki - Norlita , Wiwik; Isnaniar; Fia Monika (As-Shiha: Jurnal Kesehatan, 2024)
Indonesia is ranked 7th among 10 countries with the highest number of sufferers, which is 10.7 million, while in 34 provinces in Indonesia the highest diabetes mellitus is in East Nusa Tenggara Province, which has a prevalence of 0.9 percent, followed by Maluku and Papua at 1.1 percent, while Riau Province is in 21st position with a total of 1.8 percent. Instruments: This research was conducted at the Payung Sekaki Health Center in Pekanbaru City. When this research was carried out on July 10-11 2023. The research design used in this study was a descriptive method. The sample in this study were all respondents who had a history of diabetes mellitus at the Payung Sekaki Health Center in Pekanbaru City with a total of 30 respondents. The sampling technique used was accidental sampling. Research Results The age of the majority of respondents ranged from 56 – 60 years, DM sufferers who were taken as respondents in this study were mostly women, the education level of the respondents who were the samples of this study were mostly high school and equivalent, the work of most of the respondents was as entrepreneurs, and had suffered from diabetes for a long time most of which are < 1 year. Diabetics at the Payung Sekaki Health Center already have a good diet, do not have good physical activity, take diabetes medication as recommended, and the majority do not smoke. Overall, the lifestyle of people with diabetes mellitus at the Payung Sekaki Health Center is classified as not good. Conclusion the description of the lifestyle of people with diabetes mellitus at the Payung Sekaki Health Center in Pekanbaru City is mostly in the unfavorable category. Where these factors are age, education, and long suffering from DM. The older, the higher the education, and the longer suffering from DM, the better a person will change his lifestyle.